An initial randomized controlled trial of behavioral activation for treatment of concurrent crystal methamphetamine dependence and sexual risk for HIV acquisition among men who have sex with men. Issue 9 (2nd September 2019) - Mimiaga, Matthew J.; Pantalone, David W.; Biello, Katie B.; Hughto, Jackie M. White; Frank, John; O'Cleirigh, Conall; Reisner, Sari L.; Restar, Arjee; Mayer, Kenneth H.; Safren, Steven A.
ABSTRACT: Men who have sex with men (MSM) continue to be the largest risk group for HIV infections in the U.S., where crystal methamphetamine abuse heightens risk for HIV infection through greater engagement in condomless anal sex (CAS). Existing treatments lack attention to replacement activities or the role of depressed mood. Behavioral activation (BA) is an evidence-based approach for depression that involves identifying and participating in pleasurable, goal-directed activities. We hypothesize, for MSM abusing crystal methamphetamine, re-learning how to engage in non-drug-using aspects of life would facilitate their ability to benefit from sexual risk reduction (SRR) counseling. Project IMPACT was a pilot randomized-controlled-trial. Forty-six MSM at sexual risk of acquiring HIV who met DSM-IV criteria for crystal methamphetamine dependence were enrolled. Of those MSM, 41 were randomized: 21 were assigned to the intervention, two sessions of SRR, ten sessions of BA with SRR, and one session of relapse prevention; 20 participants were assigned to a control condition (two sessions of SRR). At the acute post-intervention visit, intervention participants reported an average of 3.2 CAS acts with men who were HIV-infected or whose status they did not know, compared to 4.5 among control participants ( β  = −0.36; 95% CI: −0.69, −0.02; p  = 0.035). At the 6-month post-intervention visit, intervention participants reported 1.1 CAS acts with men who were HIV-infected or whose status they did not know compared to 2.8 among control participants ( β  = −0.95; 95% CI: −1.44, −0.46; p  < 0.0001). Similarly, intervention participants reported 1.0 CAS acts under the influence of crystal methamphetamine with men who were HIV-infected or whose status they did not know compared to 2.5 among control participants ( β  = −0.87; 95% CI: −1.38, −0.36; p  = 0.0005). Lastly, intervention participants reported more continuous days abstaining from crystal methamphetamine compared to control (50.1 vs. 39.0, respectively) ( β  = 0.25; 95% CI: 0.16, 0.34; p  < 0.0001). Findings are encouraging, provide evidence of feasibility and acceptability, and demonstrate initial efficacy for reducing sexual risk for HIV and crystal methamphetamine use.